Review and Quantitative Analysis of Indices of Climate Change Exposure, Adaptive Capacity, Sensitivity, and Impacts - Füssel, Hans-Martin (Washington, DC: World Bank, 2012)
Adaptation to climate change is necessary, in addition to mitigation of climate change, to avoid unacceptable impacts of anthropogenic climate change [IPCC 2007]. UNFCCC Article 4 requires developed countries to assist developing countries that are "particularly vulnerable" to climate change in meeting costs of adaptation to its adverse effects. As a result, three funds have been established under the UNFCCC and Kyoto Protocol to provide financial resources for assessing, planning, and implementing adaptation measures in developing countries. Further adaptation funding is provided bilaterally and by multilateral institutions including the World Bank. The ambiguous and imprecise language used in the UNFCCC does not provide operational definitions for key concepts, including the identification of "particularly vulnerable" countries. This document discusses how science-based indicators of vulnerability to climate change and of adaptability can inform the prioritization of adaptation assistance from a global adaptation fund.